The CSI construction product representation practice guide (John Wiley & Sons, Inc., 2013)
"This book offers comprehensive, authoritative coverage of best practices for effective construction product representation. Readers will find complete guidance on how to prepare and use documents, how to choose the appropriate products for a given project, and what role to play in the construction process and in an Integrated Product Delivery (IPD) workflow. A must-have resource for anyone studying for the Certified Construction Product Representative (CCPR) Exam, the book also features a companion website with a PDF file of the book as well as CSI format documents, such as Uniformat and Sectionformat/Pageformat"--